IMPLEMENTASI TEORI POLYA PADA MATERI KELILING PERSEGI PANJANG GUNA MENINGKATKAN PEMAHAMAN BELAJAR SISWA SEKOLAH DASAR - Nadhifah, Dinah; Andriani, Pipi (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2023)
This research aims to describe and document the implementation of Polya’s theory on the circumference of rectangular flat shapes to improve elementary school students’ learning understanding. This research uses a qualitative approach with descriptive methods. The data collection techniques in this research are observation and documentation. The subjects in this research were 6 elementary school (SD) students who took part in research results, learning using Polya theory in the material around rectangular flat shapes can improve students’ understanding of more complex learning, namely: 1) students’ orientation to the problem, 2) organizing students to study, 3) guiding individual and group investigations, 4) analyse and evaluate the problem solving process. The stage of guiding individual and group investigations contains Polya’s four steps, namely: a) understanding, b) planning, c) implementation, and d) assessment.